Potential protective effects of rhEGF against ultraviolet A irradiation-induced damages on human fibroblasts - Kim JM; Choo JE; Kim KN; Kim YS (Dove Medical Press, 2018)
Ji Min Kim,1 Jung Eun Choo,1 Ki Nam Kim,1 Yang Seok Kim2 1Life Science Research Institute, Daewoong Pharmaceutical Co.,Ltd., Yongin, Korea; 2Department of Science in Korean Medicine, Kyng Hee University, Seoul, Korea Background: Ultraviolet A (UVA) rays reach the dermal skin layer and generate oxidative stress, DNA damage, and cell inflammation, which in turn lead to photo-aging and photo-carcinogenesis. While there have been many studies about the beneficial effects of topical epidermal growth factor (EGF) treatment in the healing of wounds, the effect of EGF on UVA-induced skin irritation remains unknown. To clarify the effects of EGF on UVA-induced skin damage, it was investigated whether EGF signaling can affect intracellular reactive oxygen species (ROS) and DNA damages in UVA-irradiated human dermal fibroblasts. Materials and methods: Fibroblasts cultured with or without rhEGF were UVA-irradiated at 40 mJ/cm2 twice per day for 5 days. After the irradiation, the intracellular ROS levels and expression of catalase and superoxide dismutase-1 (SOD-1) in the fibroblasts were ascertained. Further investigation to determine the effects of EGF on UVA-induced DNA damage, including a single cell gel electrophoresis assay and an enzyme-linked immunosorbent assay (ELISA), was carried out. Moreover, the NF-κB activity was ascertained in order to investigate the effects of EGF on UVA-irradiated fibroblasts. Results: As a result, it was revealed that recombinant human EGF (rhEGF) inhibited UVA-increased intracellular ROS in the fibroblasts and increased the expression of catalase and SOD-1. Moreover, in UVA-irradiated fibroblasts, the longest DNA-damaged tails were observed, but this phenomenon was not detected in cells cotreated with both UVA and rhEGF. Also, it was observed that DNA damage induction, including that of cyclobutene pyrimidine dimers, pyrimidine (6-4) pyrimidone photoproducts, and 8-hydroxy-2-deoxyguanosine, was caused by UVA irradiation. Similar to previous results, it was downregulated by rhEGF. Furthermore, rhEGF also inhibited NF-κB gene expression and the NF-κB p65 protein level in the nucleus induced by UVA irradiation. Conclusion: These results suggest that EGF might be a useful material for preventing or improving photo-aging. Keywords: epidermal growth factor, UVA, catalase, superoxide dismutase-1, cyclobutane pyrimidine dimers, pyrimidine (6-4) pyrimidone photoproducts, 8-hydroxy-2 -deoxyguanosine